Respuesta :

Hello there!

Answer: ⇒⇒⇒⇒⇒⇒ =3x+3

_________________________________________________________

Step-by-step explanation:

First you had to distribute parenthesis.

[tex]-(x+1)[/tex]

[tex]=-(x)-(1)[/tex]

Then apply minus-plus rules.

[tex]+(-a)=-a[/tex]

[tex]=-x-1[/tex]

[tex]=4-x-1+4x[/tex]

Simplify.

[tex]4-x-1+4x=3x+3[/tex]

[tex]4-x-1+4x[/tex]

Group like terms:

↓↓↓↓↓↓↓↓↓↓↓

[tex]=-x+4x+4-1[/tex]

Then add similar elements.

[tex]-x+4x=3x[/tex]

[tex]=3x+4-1[/tex]

Add and subtract by the number.

[tex]4-1=3[/tex]

[tex]3x+3[/tex]

[tex]=3x+3[/tex]

_____________________________________________________________

Hope this helps!

Thank you for posting your question at here on brainly.

Have a great day!

-Charlie

____________________________________________________________